The Content Validity Of The English Final Test Items InUN SMK Dwija Dharma Boyolali 2010-2011 Academic Year Based On School Based Curriculum And The Distribution Of Their Cognitive Level - Murdiningsih, Dewi Endah (2012)
The aim of the research is to describe the content validity of the English Final Test Items in UN SMK DWIJA DHARMA BOYOLALI 2010-2011 academic year based on School based Curriculum. The content validity is seen from the distribution of their cognitive level. The data sourceof the research are the English Final test items in UN SMK DWIJA DHARMA BOYOLALI 2010-2011 academic year. There are 35 items for each of administration and the total of the test are 105 items. This research used two parameters in this research based on School based Curriculum and the distribution of their cognitive level by Bloom's Taxonomy. In analyzing the data, the writer uses interpretation method. The research describe the English Final test items in UN SMK DWIJA DHARMA BOYOLALI 2010-2011 academic year based on School based Curriculum. and the distribution of their cognitive level in Bloom's Taxonomy. The process of the data collecting technique in this research are taken from document of English Final test items in UN SMK DWIJA DHARMA BOYOLALI 2010-2011 academic year. The result of this research shows that the Content Validity of the English Final Test Items in UN SMK DWIJA DHARMA BOYOLALI 2010-2011 based on School based Curriculum, yes it is does. It is valid because it is correspond with indicators on a syllabus in school. The data consist English Final test items can be classified three parts. They are incomplete dialogue, error recognition and reading comprehension.